Estudo de reconstrução (2x6) em GaSb (001) - Oliveira, Joao Batista de (2004)
The present work represents a theorical study of the GaSb-(2x6) surface reconstructions. The surface atomic geometry and the electronic structures of three surface reconstruction models were investigated and the energetically more stable model was determined. One of the model studed was proposed by Sieger, from experimental results and shows a liberations of two electrons per (2x6) unit cell. The other two models were proposed by us as modifications of Sieger model. The first model proposed by us was denominated Model I (M-I) and obeys the el ectron couting model. The second model proposed by s was called Model II (M-II) and shows the absence of two electrons per (2x6) unit cell. The computacional pach fhi98md [2] was used to carried out ab initio self-consistent calculations within the Density Functional Theory (DFT). The Kohn-Sham equations were solved by employing fully separable norm-conserving pseudopotentials as proposed by Kleinman and Bylander. The exchange-correlation term was treate whitin Generalized Approximation (GGA). From our results, we concluded that Sieger model is energetically more stable than the M-I model by 0,82 eV and is energetically more stable than the M-II model by 0,86 eV. Total charge density analisys show that the formation of the Sb double-layer at the GaSb(001)-(2x6) surface can be suported by the covalent character of the bondings between superficial Sb atoms and subsuperficial atoms, as strong as the covalent bonding between the Sb dimers.